Ancient cardiac myxomas – another point of view in the light of tetraspanins - Lewitowicz, Piotr; Bernaczyk, Piotr; Horecka-Lewitowicz, Agata; Leszczyńska, Urszula; Reszeć, Joanna; Hirnle, Tomasz; Wincewicz, Andrzej (Polish Journal of Pathology, 2016)
Myxomas are the most common non-invasive but life-threatening cardiac neoplasms due to obstruction of heart chambers and risk of embolism in a manner resembling thromboembolism as well. They can occasionally disseminate via their detached fragments into the bloodstream to seed and grow as secondary still benign tumors. In this study we evaluated morphological and clinical aspects of 14 ancient, degenerated left or right-sided cardiac atrial myxomas with expression of CD9 and CD63, which are found to contribute to platelet activation, aggregation and, as a result, intratumoral thrombosis or fragmentation. The appearance of tumors varied from sessile to polypoid revealing that a higher rate of endocardial thrombosis was associated with sessile compared to polypoid myxomas and left-sided tumors compared to right-sided ones in our study. In the general aspect of ancient calcifications, amorphous calcification with intra-tumor thrombosis was noted more frequently in sessile tumors, while well-formed osseous metaplasia was usually a feature of polypoid tumors. In our material osseous metaplasia did not coexist with massive thrombosis and was found in polypoid, pedunculated myxomas. Most importantly, CD9 overexpression was recorded in every studied myxoma and CD63 gave a weak reaction in myxoma cells.